2020
DOI: 10.3126/janr.v3i1.27177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different tillage practices and nitrogen level on wheat production under inner terai of Nepal

Abstract: A field experiment was conducted to evaluate the plant height, yield and yield attributes of wheat under different tillage practices and nitrogen level at Dang, Nepal during winter season 2018-19. The experiment was laid out in split plot design with two tillage practices viz. zero tillage and conventional tillage as main plot factor and four level of N viz. 50 kg ha-1, 75 kg ha-1, 100 kg ha-1and 125 kg ha-1 as sub plot factor and each replicated thrice.  The result revealed that there is no significant relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…The extent of the positive impact of straw-return to the field or residue incorporation into the field and notill soil practice remains a subject of discussion because experiments conducted in different types of soil and climatic conditions have led to unconvincing findings (Han et al, 2020;Pittelkow et al, 2015;Ogle et al, 2012). The present findings indicate that in comparison with CT, the different conservation tillage practices of NTS, CTS and NT considerably improved the agronomic traits of wheat, as confirmed by other researchers (Bartaula et al, 2020;Hirzel et al, 2020;Han et al, 2020;Yang et al, 2016;Farooq et al, 2011;Devita et al, 2007).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The extent of the positive impact of straw-return to the field or residue incorporation into the field and notill soil practice remains a subject of discussion because experiments conducted in different types of soil and climatic conditions have led to unconvincing findings (Han et al, 2020;Pittelkow et al, 2015;Ogle et al, 2012). The present findings indicate that in comparison with CT, the different conservation tillage practices of NTS, CTS and NT considerably improved the agronomic traits of wheat, as confirmed by other researchers (Bartaula et al, 2020;Hirzel et al, 2020;Han et al, 2020;Yang et al, 2016;Farooq et al, 2011;Devita et al, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…There were multiple factors responsible for the improved wheat agronomic performance. Firstly, soil nutrient accumulation and the availability of nutrients to plants may increase through straw-return or straw incorporation because straw return is essential for plant nutrient return to the soil, this contributes to improved crop production (Bartaula et al, 2020;Zhao et al, 2019). Secondly, wheat-straw includes a considerable amount of organic matter which contributes to the quality of the soil leading to improved crop yield attributes (Yang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This might have outcome in increased number of individual grain per panicle and test weight expressed in terms of grain weight per panicle (Goutami et al, 2015). These results were in consonance with the findings of Patil (2013), Mishra et al (2015) and Bartaula et al (2019).…”
Section: Resultssupporting
confidence: 92%
“…The plant population was higher in other treatments over CP, which might be the result of intervention of one or more climate smart practices. Bartaula et al [40] and Khalid et al [26] reported that effective tiller per square meter was higher for zero tillage practice compared to conventional tillage. The higher plant height was observed in the treatments including climate smart interventions compared to CP.…”
Section: Discussionmentioning
confidence: 99%
“…Difference in TKW was observed as an effect of location and treatment. Several previous studies have shown that TKW is affected by the location, tillage, and N management practices [40,43]. Rieger et al [43] found that no-till system resulted in lower TKW compared to conventional tillage.…”
Section: Discussionmentioning
confidence: 99%